KINERJA KARYAWAN PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA SIAK DALAM PENYEDIAAN KEBUTUHAN AIR BERSIH DI KOTA PEKANBARU - Istiani, Fifin; Harahap, Tuti Khairani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
One of the obligations of local government in public administration is to carry out obligatory tasks such as providing clean water for the community. As ststed in the 1945 constitution article 33 paragraph 3 that the earth, water, and natural resources contained there in are controlled by the state and in use for the greatest possible for the welfare of the people. To carry out these obligations, the government’s performance is necessary to achieve as the objectives set by the state.Performance is the result of work in quantity achieved by employess in performing their duites which related to the responsibilities are given to them (Mangkunegara 2012:9). PDAM Tirta Siak is a Regional Owned Enterprise (BUMD) engaged in providing services and clean water supply needs to the community in the city of Pekanbaru.The research is based on the facts that occurred in PDAM Tirta Siak has not done clean water supply for the city of Pekanbaru community thoroughly even every year its customers decreased.through qualitative approach, the purpose of this research is to know how is the performance op PDAM Tirta Siak employess and to identify factors affecting the performance of PDAM Tirta Siak in fulfilling the need of clean water in Pekanbaru. Which is set in Kepmendagri Number 47 of 1999 on PDAM performance assessment guidance in article 3 that is financial aspect, operational aspect, and administration aspect. To strengthen the findings of Agus Dwiyanto theory in the research into performance consisting of effectiveness, responsiveness, and akuntability.The result of this study found that employee performance PDAM Tirta Siak not done to the fullest.In this research also found some inhibiting factors in the provision of clean water include funding factors, facilities and infrastructure, and lack of professional human resources.Keywords: Employee Performance, Tirta Siak Water Supply Company, Clean Water Supplies Requirement